Participatory vulnerability assessment and planning of adaptation to climate change in the Yatenga, Burkina Faso - Somda, Jacques; Sawadogo, I.; Sawadogo, Mahamadou; Zougmoré, Robert B.; Bationo, B. André; Moussa, Abdoulaye S.; Nakoulma, G; Sanou, J; Barry, S; Sanou, AO; Somé, Léopold (2014)
The impacts of climate change on food security are a thorny issue, especially in countries with marginal and volatile weather conditions. Burkina Faso is one of those countries where agriculture, mainly rain- fed type, is highly dependent on agro-climatic parameters such as rainfall, temperature, sunshine, wind, etc. In Yatenga province, located in the northern region of Burkina Faso, the agro climatic parameters are undergoing major changes over the years. The autonomous adaptation to climate change and climate variability has been implemented by the people through the diversification of their activities, irrigation, water management, risk management and disaster insurance. French version: http://hdl.handle.net/10568/35178